Obraz niedoli w pieśni weselnej, czyli epitalamia Drakoncjusza jako przykład jego nowatorstwa - Cichoń, Natalia (Collectanea Philologica, 2015)
In this paper I examine Dracontius’ distinctiveness from other Latin and Greek poets writing epithalamia. He is not just another author of original wedding songs but surprises in many ways and can be found unusual even exploring a genre that did not have one well-defined model. To prove his unconventionality and uniqueness I firstly give a detailed analysis of both wedding songs by Dracontius I demonstrate the poet’s dependence upon earlier literature, explain the metaphors he used and discuss his reinterpretations of different themes introduced already by the poets before him. Then I add all my conclusions concerning Dracontius’ originality in comparison with his predecessors.